2011
DOI: 10.3109/15563650.2011.583251
|View full text |Cite
|
Sign up to set email alerts
|

Severe propranolol and ethanol overdose with wide complex tachycardia treated with intravenous lipid emulsion: A case report

Abstract: We believe that lipid emulsion had a beneficial effect in the treatment of propranolol toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 10 publications
1
26
0
3
Order By: Relevance
“…This response or 'plateau effect' appears to be present in other studies [15]. Jovic-Stosic et al recently reported the successful use of Intralipid at doses exceeding 24 mg.ml )1 in a patient presenting with severe propranolol and ethanol toxicity [33]. Study 3 suggests that the lipid solubility of the drug administered in overdose (as suggested by the log P value) may give an indication of the potential benefit of lipid emulsion; there may be little benefit in administering lipid emulsion to treat toxicity from lipid insoluble drugs [34].…”
Section: Discussionmentioning
confidence: 84%
“…This response or 'plateau effect' appears to be present in other studies [15]. Jovic-Stosic et al recently reported the successful use of Intralipid at doses exceeding 24 mg.ml )1 in a patient presenting with severe propranolol and ethanol toxicity [33]. Study 3 suggests that the lipid solubility of the drug administered in overdose (as suggested by the log P value) may give an indication of the potential benefit of lipid emulsion; there may be little benefit in administering lipid emulsion to treat toxicity from lipid insoluble drugs [34].…”
Section: Discussionmentioning
confidence: 84%
“…Therapieerfolge sind beim Einsatz von Glucagon (50-150 μg/kgKG, [357][358][359][360][361][362][363][364][365][366][367][368][369][370]), hochdosierter Insulin-und Glukosegabe [371][372][373], Lipidemulsionen [374][375][376][377], Phosphodiesterasehemmern [378,379], extrakorporaler Unterstützung und IAPB-Einsatz (intraaortale Ballonpumpe, [380][381][382] …”
Section: Beta-blockerunclassified
“…Signs and symptoms of toxicity are generally non-specific and may include coma, generalized tonicclonic seizures, cardiac arrhythmias, and respiratory distress [3][4]. Beta-blocker overdose is not uncommon, given its widespread use.…”
Section: Introductionmentioning
confidence: 99%